Exploring Local Wisdom in Prohibitive Speech Acts: A Sociocultural Study of the Kerinci Community - Sari, Ayu Permata; Susmita, Nelvia (JOLLT Journal of Languages and Language Teaching, 2025)
Research on speech acts has been extensively conducted by scholars; however, studies specifically focusing on prohibitive speech acts, especially regarding the forms and functions of local wisdom values within these acts, are still quite rare. This research is aimed at exploring the forms and functions of local wisdom values in the prohibitive speech acts of the Kerinci community. This research employed a descriptive qualitative method which involved ten informants from Pondok Tinggi Village and Sungai Penuh Village, Kerinci Regency, Jambi Province. The data were collected using observation, note-taking, and recording for two months. The data were analyzed qualitatively by using an interactive model. The results show that the forms of local wisdom values in the prohibitive speech acts of the Kerinci community were prohibitive speech acts with consequences and without consequences. These prohibitions encompass local wisdom values across moral, respectful behaviour, health, safety, social harmony, responsibility, ethics, and environmental stewardship. Moreover, the functions of local wisdom values in the prohibitive speech acts in the Kerinci community serve as a means of behaviour control and convey local wisdom values that support moral education and environmental preservation. Furthermore, the functions emphasize the importance of integrating local values into education to enhance community awareness of the environment and social relationships. Thus, integrating these local values into educational contexts could foster community awareness of environmental and social responsibilities, supporting cultural preservation and reinforcing the importance of these values for future generations.Â 